MEMORY AND LANGUAGE: a study on Cordel's brochures - Camargo de Oliveira, Heloa Cristina [UNESP]; Almeida Junior, Oswaldo Francisco de [UNESP] (Univ Federal Campina Grande, 2015)
It is presented memory characteristics as opposed to history, their social context and their difficulty of expression (especially in relation to oblivion), in order to stress the importance and complexity of memory. To target such a study, Cordel's works was chosen, a discussion of these as memory preservation works, from the identification of the role of language in the exhibition context of this literature characteristic. Cordel molded itself with composition of various language tools and approaches, and this gives rise to the question of whether this composition can weaken or enhance memory. From the studies of this constant linguistic evolution, new questions are put forward to the use of language - in its both meanings - and memory preservation. As a result from literature researches, one can explore the issue and conclude that the cordel literature has the peculiarity of working with language in a plentiful way, however, this did not protect these works from oblivion.
Keywords: Memory; Language; Cordel's Brochures